Mechanistic understanding of perianth traits hindering pollination in Aristolochia contorta Bunge - Park, Si-Hyun; Kim, Jae Geun (Frontiers in Plant Science, 2023)
Insects are vital pollinators for angiosperms, playing a crucial role in their reproductive success and fruit production. Aristolochia contorta is a perennial herbaceous vine that occurs in fragmented populations across East Asia. One notable feature of this plant is its trap flower, which employs a unique mechanism to attract, trap, retain, and release insects, ensuring effective pollination. The presence of this trap flower significantly influences the pollination system of A. contorta. Field surveys and pollination experiments were conducted to understand the processes and effectiveness of its pollination mechanism. It was allogamous and was pollinated by the species from Ceratopogonidae. During the insect attraction stage, 11.57% of the flowers contained insects, primarily Ceratopogonidae spp. Most Ceratopogonidae spp. concentrated in few flowers, indicating that although overall attraction might be modest, specific flowers acted as significant focal points for gathering. Trichomes effectively trapped Ceratopogonidae spp. inside flower tubes. In the retention stage, 26.16% of Ceratopogonidae spp. were loaded with pollen grains, but only 7.91% of those exited the flowers in the release stage. The sticky texture of the perianth’s internal cavity posed challenges during this release, leading to adhesion and clogging of the narrow perianth tube. Consequently, a significant portion of Ceratopogonidae spp. became trapped on the perianth wall and perished. This highlights that despite the significant energy and resources invested in flower development, the perianth contributes to the low pollination effectiveness. This study revealed additive factors with negative effects on pollination, including the densely clustered distribution of its pollinators within only a few flowers, insufficient pollen loading onto pollinators, hindered release of entrapped pollinators due to the perianth adhesive surface, and a high rate of defective pollen grains in A. contorta. These factors account for the observed phenomenon of low fruit set (7.7%) and contribute to the diminished rate of sexual reproduction in A. contorta populations. This might lead the species to heavily rely on asexual reproduction, which could potentially lead to gene erosion within populations. The implications of these findings extend to the ecological and conservation aspects, emphasizing the need to understand and conserve the unique pollination system of A. contorta.